Characterization of Nora Virus Structural Proteins via Western Blot Analysis - Brad L. Ericson; Darby J. Carlson; Kimberly A. Carlson (Scientifica)
Nora virus is a single stranded RNA picorna-like virus with four open reading frames (ORFs). The coding potentials of the ORFs are not fully characterized, but ORF3 and ORF4 are believed to encode the capsid proteins (VP3, VP4a, VP4b, and VP4c) comprising the virion. To determine the polypeptide composition of Nora virus virions, polypeptides from purified virus were compared to polypeptides detected in Nora virus infected Drosophila melanogaster. Nora virus was purified from infected flies and used to challenge mice for the production of antisera. ORF3, ORF4a, ORF4b, and ORF4c were individually cloned and expressed in E. coli; resultant recombinant proteins purified and were used to make monospecific antisera. Antisera were evaluated via Western blot against whole virus particles and Nora virus infected fly lysates. Viral purification yielded two particle types with densities of ~1.31 g/mL (empty particles) and ~1.33 g/mL (complete virions). Comparison of purified virus polypeptide composition to Nora virus infected D. melanogaster lysate showed the number of proteins in infected cell lysates is less than purified virus. Our results suggest the virion is composed of 6 polypeptides, VP3, VP4a, two forms of VP4b, and two forms of VP4c. This polypeptide composition is similar to other small RNA insect viruses.